التنظيم القانوني لقسمة الملكية الشائعة في التشريع الجزائري - حمده, عمار (جامعة الوادي University of Eloued, 2017)
يميل الإنسان بفطرته إلى حب الاستئثار بالملكية ملكية فردية لا ينازعه في التصرف فيها احد، ويعد الشيوع حالة مؤقتة، وضع مقلق وغير مرغوب فيه،لذلك يلجا الشركاء إن آجلا أو عاجلا إلى قسمة المال الشائع فيما بينهم إما اتفاقيا عند إجماع اتفاقهم على ذلك أو باللجوء إلى القضاء عند رغبة احد الشركاء أو بعضهم الخروج من الشيوع، والقسمة هي من أهم أسباب إزالة الشيوع وإفراز الملكية الشائعة إلى حصص منفصلة، ولقد قسم المشرع الجزائري الشيوع الى نوعين شيوع إجباري وشيوع اختياري،فالأول غير قابل للقسمة ،والثاني قابل للزوال بالقسمة كالميراث مثلا. وتضمن القانون المدني، قواعد تنظم القسمة،منها قواعد تتعلق بقسمة المهاياة،أو القسمة الاستغلالية أو قسمة المنافع ،وقواعد تتعلق بالقسمة الاتفاقية وشروطها ، أهمها إجماع كافة الشركاء على ذلك، وقواعد تتعلق بالقسمة القضائية ،وطرق القسمة تكون إما عينيا إن كان المال الشائع يمكن فرزه حصصا،أو بالتصفية أي بيعه بالمزاد العلني وتقسيم ثمنه على الشركاء عند عدم إمكانية قسمته عينيا ،ودعوى إبطال القسمة الاتفاقية لغبن، وهو ما سنتناوله بالبحث في هذه المذكرة : Man tends to monopolize property as an individual good and does not accept his sharing with others. Indivision is a temporary case, a worrying and unacceptable state. The co-owners are used sooner or later to share it by mutual consent of the various parties or by recourse to justice in the event that one of the co-owners wants to leave the undivided ownership. Sharing is one of the essential causes of the disappearance of indivision and its subdivision. The Algerian jurist has divided indivision into two distinct categories: the first is indivisible while the second can be shared as inheritance. The civil code contains rules governing the sharing, including the one inherent in the provisional or exploitation sharing and that inherent to the conventional or amicable sharing, the most important of which is the collective consent of the co-owners and to introduce other sharing rules. judicial. In this case the partition is either a partition by nature if the undivided good allows it or by licitation and then share its pecuniary value for the benefit of coheirs when circumstances do not allow sharing by nature. There are other rules inherent to the nullity of the conventional sharing for injury and its consequences on it. This is what we will discuss in this study
/قانون عقاري
Keywords: المكية الشائعة ، التشريع،النظام اقانوني; Common property, legislation, legal system